Gearing Toward Sustainability: Knowledge and Compliance of Local Tourism Business Operators in Southern Philippines on the Mandatory Regulations - Jesther Nasa-an; Dankyle Barbarino; Jairus Goring; Justine Cristobal; Yammie Daud (SHS Web of Conferences)
This study examines the knowledge and compliance levels of local tourism business operators in Southern Philippines concerning mandatory sustainability regulations in terms of licensing and accreditation, sustainable tourism development, preservation of cultural heritage, community involvement initiatives, and consumer protection policies. As the tourism industry thrives, sustainable practices have become of greater importance to ensure environmental preservation and community well-being. A quantitative method was employed to investigate the extent of compliance of these local business operators about their knowledge of the existing mandatory regulations. The study reveals gaps in knowledge and different levels of compliance by employing a combination of surveys and interviews with the local business operators. Through a quantitative approach involving surveys, focus group discussions, and data analysis, key findings reveal a strong understanding of supporting cultural events among operators but a moderate knowledge of other regulatory aspects. The research highlights varying levels of knowledge and compliance with licensing and accreditation requirements, emphasizing the importance of responsible tourism practices for environmental and cultural preservation. The study recommends targeted educational programs, streamlined regulations, and stakeholder partnerships to enhance operators’ compliance and support sustainable tourism development. By bridging knowledge gaps, addressing barriers to compliance, and implementing tailored interventions, strengthen its regulatory framework, foster industry professionalism, and advance toward sustainable tourism practices. This research contributes valuable information to the regulatory landscape and offers practical recommendations for promoting responsible tourism management and economic growth in the region.